2020
DOI: 10.1136/jech-2019-213093
|View full text |Cite
|
Sign up to set email alerts
|

Variations in neonatal mortality, infant mortality, preterm birth and birth weight in England and Wales according to ethnicity and maternal country or region of birth: an analysis of linked national data from 2006 to 2012

Abstract: BackgroundRisks of adverse birth outcomes in England and Wales are relatively low but vary across ethnic groups. We aimed to explore the role of mother’s country of birth on birth outcomes across ethnic groups using a large population-based linked data set.MethodsWe used a cohort of 4.6 million singleton live births in England and Wales to estimate relative risks of neonatal mortality, infant mortality and preterm birth, and differences in birth weight, comparing infants of UK-born mothers to infants whose mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 22 publications
1
12
1
1
Order By: Relevance
“…The main outcome variable was the registered birthweight, from the Spanish vital statistics data, for the period 2017–2017. The mean birthweight of infants born to immigrant mothers from different origins is a valid indicator of perinatal health, as well as a strong predictor of mid- and long-term health-related outcomes as has been shown in previous research [ 13 , 24 , 38 ]. It should be noted that there is a large correlation (point-biserial correlation coefficient: − 0.58, 95% CI: − 0.58 to − 0.58) between the mean birthweight at term and low birthweight (< 2500 g).…”
Section: Methodsmentioning
confidence: 67%
“…The main outcome variable was the registered birthweight, from the Spanish vital statistics data, for the period 2017–2017. The mean birthweight of infants born to immigrant mothers from different origins is a valid indicator of perinatal health, as well as a strong predictor of mid- and long-term health-related outcomes as has been shown in previous research [ 13 , 24 , 38 ]. It should be noted that there is a large correlation (point-biserial correlation coefficient: − 0.58, 95% CI: − 0.58 to − 0.58) between the mean birthweight at term and low birthweight (< 2500 g).…”
Section: Methodsmentioning
confidence: 67%
“…Short stature is more common in boys than girls in LMICs, and it has been postulated that this is due to higher rates of adverse birth outcomes and increased vulnerability to infection and other morbidity during infancy in boys [ 27 , 28 ]. These data might suggest that this is not a reasonable explanation for sex differences in referral patterns in the UK setting, as the incidence of adverse birth outcomes and childhood infections are higher for boys in the UK [ 29 , 30 ]. It should be noted that the use of UK90 growth references means that rates of short stature in girls and boys will be slightly different to those calculated using WHO standards, which are used in most of the international literature.…”
Section: Discussionmentioning
confidence: 99%
“…The main characteristics of the selected studies have been outlined in Table 1 . The studies were conducted in Europe ( n = 37; Spain [ 23 , 33 ], Finland [ 25 , 34 ], Israel [ 9 , 15 ], Turkey [ 22 , 24 , 35 38 ], Sweden [ 12 , 13 , 39 , 40 ], Norway [ 16 , 19 , 41 45 ], Belgium [ 17 , 18 , 45 , 46 ], United Kingdom [ 45 , 47 ], Netherlands [ 20 , 45 ], Denmark [ 45 , 48 ], Switzerland [ 45 ], Austria [ 45 ], Germany [ 45 ] and Italy [ 49 ]), America ( n = 8; Canada [ 21 , 26 , 50 ], USA [ 51 53 ] and Argentina [ 4 , 54 ]), Australia ( n = 5) [ 8 , 10 , 11 , 14 , 55 ]), and Taiwan ( n = 1) [ 56 , 57 ]. The results of quality appraisals of the included studies have been summarized in Supplementary Tables S1, S2 .…”
Section: Resultsmentioning
confidence: 99%
“…A total of 17 studies [ 4 , 8 , 10 , 11 , 26 , 33 , 34 , 42 , 43 , 46 , 47 , 50 54 , 56 ] reported the perinatal mortality among 4,399 out of 487,508 immigrant women and 30,838 out of 3,859,199 native-origin women. However, heterogeneity (I-squared = 87.1%) without publication bias (Harbord test p value = 0.340) was found across the studies.…”
Section: Resultsmentioning
confidence: 99%